The Use of English Addressing Terms on Facebook - Arumi, Sihindun; Giyatmi, G; Wijayava, Ratih (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
This research was such a kind of descriptive qualitative design. It aimed to recognize the types of English addressing terms used on facebook and describe the function of English addressing terms used on faceboook. Data of the research were English addressing terms used by facebook users, written either on status or comments. Data were collected through observation and documentation techniques. In this case, English addressing terms were observed from the friends’ status and comments on facebook. Then, they were documented using print screen or much screen. Print screen is a facility to take picture through computer, while munch screen is a facility to take picture through handphone. The result of the research showed that there are some types of English addressing terms used on facebook, such as full name (1), nick name (2), title and names (8), familizer (1), family terms (14), endearments (20), nouns (4), and pronouns (3). The addressing terms on facebook present 17 functions, such as tagging, showing familiarity, fostering familiarity, expressing empaty, showing symphaty, delivering information, delivering dakwah/ religious messages, showing politeness, maintaining social relationship, showing family relationship, delivering appeal, expressing affection, expressing dissapointment/anger, showing hope, showing specification, and showing worry or confusion. The results of the research are essential in identifying the development of English in Indonesia, especially relating to addressing terms. They are also important to measure the instance of politeness used in writing status-comment on facebook.